(untitled) (Annual of the Faculty of Philosophy in Skopje, 2007)
In this article, the author offers a possible classification of Mycenaean personal names and their forms in Aiolian and Ionian on the basis of the dialectological analysis of the Greek prefix άρί- / έρί-, ’much, very’. In this article, the author suggests that the Mycenaean personal name e-ri-sa-ta (KN Nc 4474) derives from έρί-, ‘much, very’and σάθη ‘männliches Glied’, i.e., е-ri-sa-ta/e-ri-sa-ta /Eri-sathäs/: *’Ερι-σάθας, from which the following forms survive in Greek as successors from the Mycenaean epoch: Έρί-σαθεύς cf, Έρι-σαΘεύς ’Απόλλων έν τη ’Αττική Hesch cf, άνδρο- σάθης, cf, sa-ni-jo / Sannios : Sanniön / : Σάννιος : Σαννίων (ΡΥAn 6) and others.